2017
DOI: 10.2147/dddt.s133814
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of wild-type and 24 CYP2D6 allelic variants on gefitinib metabolism in vitro

Abstract: BackgroundCytochrome P450 2D6 (CYP2D6), a member of the CYP450 enzyme super family, is a polymorphic enzyme that metabolizes ~25% of therapeutic drugs. CYP2D6 exhibits significant genetic polymorphisms which might cause adverse effects and therapeutic failures of some drugs.ObjectiveThe purpose of this study was to evaluate the catalytic activities of 22 novel CYP2D6 alleles (CYP2D6*87, *88, *89, *90, *91, *92, *93, *94, *95, *96, *97, *98, R25Q, F164L, E215K, F219S, V327M, D336N, V342M, R344Q, R440C, R497C) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Previously, we and others have shown that pCBs are metabolized by various human CYPs to form novel oxidized products. 23,[48][49][50] Additionally, many of the pCBs tested, including CBD have been shown to inhibit CYPs. 41 Herein, we explore the differences in pCB binding, metabolism, and inhibition of CYP2D6 and its mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we and others have shown that pCBs are metabolized by various human CYPs to form novel oxidized products. 23,[48][49][50] Additionally, many of the pCBs tested, including CBD have been shown to inhibit CYPs. 41 Herein, we explore the differences in pCB binding, metabolism, and inhibition of CYP2D6 and its mutants.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the concentrations of CBN could not be detected for CYP3A4.6, .20, and .30. Similar with ibrutinib, gefitinib, and regorafenib, CBZ was prone to substrate inhibition with K si of all tested CYP3A4 variants averaging from 3.61 to 135.07 μM.…”
Section: Resultsmentioning
confidence: 89%
“…28 Because of the significant contribution of CYP2D6 in the metabolism of drugs, discovery of its inhibitors is a key research area in drug discovery programs. 28d Furthermore, the CYP2D6 enzyme has extensively been studied for delineation of the metabolism (O-demethylation and N-demethylation) of approved drugs viz metoprolol, 29 gefitinib, 30 and natural products. 31…”
Section: Resultsmentioning
confidence: 99%
“…28 Because of the significant contribution of CYP2D6 in the metabolism of drugs, discovery of its inhibitors is a key research area in drug discovery programs. 28d Furthermore, the CYP2D6 enzyme has extensively been studied for delineation of the metabolism (O-demethylation and N-demethylation) of approved drugs viz metoprolol, 29 gefitinib, 30 and natural products. 31 To understand the observed trend in differential demethylation reactions (O vs N-demethylation) using CYP2D6-wt and CYP2D6-C (CYP2D6.10 A112V ), molecular modeling studies were conducted.…”
Section: ■ Results and Discussionmentioning
confidence: 99%